2017
DOI: 10.21010/ajtcam.v14i6.12
|View full text |Cite
|
Sign up to set email alerts
|

A Review of the Therapeutic Characteristics of Camel Urine

Abstract: Background: The therapeutic use of camel urine has been known for centuries, with evidence of its use for medicinal purposes found in early folklore. It has been used to cure different diseases; however, the significant therapeutic benefits of urine have yet to undergo rigorous scientific evaluation. In this review, a summary of the scientific evidence that supports these therapeutic actions has been presented. Materials and methods: A literature search of different electronic databases including PubMed, Medli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 33 publications
0
8
0
1
Order By: Relevance
“…In the Middle East camel excreta are traditionally used to treat various ailments and the urine of this animal has also been the subject of numerous pharmacological studies [ 89 ]. 5 Anti-microbial properties of camel urine have been demonstrated in vitro showing antifungal activity on Candida albicans and Aspergillus nige and anti-bacterial activity against multi-drug resistant pathogenic bacteria [ 90 , 91 ].…”
Section: Resultsmentioning
confidence: 99%
“…In the Middle East camel excreta are traditionally used to treat various ailments and the urine of this animal has also been the subject of numerous pharmacological studies [ 89 ]. 5 Anti-microbial properties of camel urine have been demonstrated in vitro showing antifungal activity on Candida albicans and Aspergillus nige and anti-bacterial activity against multi-drug resistant pathogenic bacteria [ 90 , 91 ].…”
Section: Resultsmentioning
confidence: 99%
“…Eine etwas appetitlichere Alternative für den neugierigen Leser könnte übrigens Kamelmilch sein, die ein ebenso interessantes Wirksamkeitsspektrum wie Kamelurin aufweist – viele der Inhaltsstoffe wie die erwähnten Antikörper und damit deren Effekte wurden auch in der Milch gefunden, auch wenn diese wohl schwieriger im großen Stil medizinisch umgesetzt werden kann .…”
Section: Abbunclassified
“…Camel urine is believed to have therapeutic effects in the treatment of cancer, diabetes, certain infectious and cardiovascular diseases as well as in the treatment of hair and skin problems. Hence, fresh urine is consumed, used to wash body and hair, and is a component in ointments (Alkhamees, 2017;Gader, 2016) for example it has been described that Bedouins in the Middle East have a daily consumption of 100 ml camel urine while a study amongst 156 Saudi cancer patients showed that 15.7% drank camel urine (Abuelgasim, 2018;Al-Yousef et al, 2012).…”
Section: Failure To Detect Mers-cov Rna In Urine Of Naturally Infectementioning
confidence: 99%